Noble gas data during SAS21 Oden cruise - Yannis Arck; Edith Engelhardt; Florian Freundt; Stefan Schäfer; Stanley Scott; Werner Aeschbach (PANGAEA, 2025)
This data set provides the final measurement results of noble gas samples taken during the Synoptic Arctic Survery 2021 in the central Arctic Ocean on the icebreaker Oden (Snoeijs-Leijonmalm et al., 2022). At six distinct stations, located in the Nansen Basin, above the Gakkel Ridge, in the Amundsen Basin, the Makarov Basin and north of the Greenland shelf, two replicate samples were taken at 11 depths covering the complete water column from the surface to the ocean floor as part of the project Ventilation and Anthropogenic Carbon in the Arctic Ocean. Samples were transferred from Niskin bottles to copper tubes under atmospheric isolation (Beyerle et al., 2000). At Heidelberg University, the samples were analyzed on a sector field mass spectrometer for the dissolved concentrations of helium, neon, argon, krypton and xenon, as well as the 3He/4He ratio, from summer 2022 until spring 2025 within several measurement runs (Schwenk et al., 2022). The obtained concentrations were converted into saturation anomalies (Jenkins et al., 2019), based on the prevailing temperature and salinity measured during the cruise for each data point respectively (Heuzé et al., 2022). If applicable, both replicate measurements are averaged and the final result is stated. These noble gas concentration and saturation data can be used to identify ocean surface processes like sea ice formation and melt, cooling of inflowing water masses or bubble intrusion caused by wind and breaking waves.